Increasing plasma glucose before the development of type 1 diabetes—the TRIGR study. Issue 7 (7th September 2021) - Ludvigsson, Johnny; Cuthbertson, David; Becker, Dorothy J.; Kordonouri, Olga; Aschemeier, Bärbel; Pacaud, Daniele; Clarson, Cheril; Krischer, Jeffrey P.; Knip, Mikael; ,
Abstract: Objective: The β‐cell stress hypothesis suggests that increased insulin demand contributes to the development of type 1 diabetes. In the TRIGR trial we set out to assess the profile of plasma glucose and HbA1c before the diagnosis of clinical diabetes compared to nondiabetic children. Research Design and Methods: A cohort of children ( N = 2159) with an affected first‐degree relative and increased HLA risk were recruited 2002–2007 and followed until 2017. To study the relationship between plasma glucose/HbA1c and the development of autoantibodies or clinical disease Kaplan‐Meir curves were developed. Mixed models were constructed for plasma glucose and HbA1c separately. Results: A family history of type 2 diabetes was related to an increase in plasma glucose ( p < 0.001). An increase in glucose from the previous sample predicted clinical diabetes ( p < 0.001) but not autoantibodies. An increase of HbA1c of 20% or 30% from the previous sample predicted the development of any autoantibody ( p < 0.003 resp <0.001) and the development of diabetes ( p < 0.002 resp <0.001. Participants without autoantibodies had lower HbA1c (mean 5.18%, STD 0.24; mean 33.08 mmol/mol, STD 2.85) than those who progressed to clinical disease (5.31%, 0.42; 34.46 mmol/mol, 4.68; p < 0.001) but higher than those who developed any autoantibody (5.10%, 0.30; 32.21 mmol/mol, 3.49; p < 0.001), or multiple autoantibodies (5.11%, 0.35; 32.26 mmol/mol, 3.92; p < 0.003). Conclusions: A pronounced increase in plasma glucose and HbA1c precedes development of clinical diabetes, while the association between plasma glucose or HbA1c and development of autoantibodies is complex. Increased insulin demand may contribute to development of type 1 diabetes.